Lac des Bois, a locality in the northern Western Interior Seaway (Canada) with Tethyan faunal connections during the Cenomanian/Turonian Thermal Maximum. (November 2018) - Cumbaa, Stephen L.; Day, Richard; Gingras, Murray; Haggart, James W.; Holmes, Robert B.; Murray, Alison M.; Schröder-Adams, Claudia
Abstract: Early Turonian fishes are known from only a few localities in the Northern Hemisphere, including three in the present-day European/Mediterranean region and three in northern Canada. One of the latter localities, Lac des Bois (66°52.087ʹ N), preserves a diverse marine fauna composed of trace fossils, foraminifera, molluscs and actinopterygian fishes including early acanthomorphs. The molluscan fauna, as well as a radiometric date from bentonites recovered from the site, support an age of latest Cenomanian/early Turonian for the locality. This interval spans the global Oceanic Anoxic Event 2, a time characterized globally by high temperatures and high carbon burial. Although the Cenomanian/Turonian boundary interval has been documented in North America in the Arctic Sverdrup Basin and the southern Interior Seaway, the present study provides the first account of a faunal assemblage that inhabited the northern Western Interior Seaway during this interval. Organic-rich shales and sandstones indicate limited organic decomposition and low oxygen conditions, although the presence of trace fossils ( Skolithos, Planolites, Taenidium and Alcyonidopsis, as well as fugichnia) indicates that the sea floor was not completely anoxic. The presence of coiled planktic foraminifera indicates warmer water and extends the known migration limit of these Tethyan-derived forms some 6° further north. Surprisingly, the fish fauna of localities in the Bohemian Cretaceous Basin (Czech Republic) bears a close resemblance to that of Lac des Bois, although acanthomorph fish have not been recorded from the former. This suggests faunal connections between the two regions, either through the northern Polar Sea, or through the postulated Hudson Strait.